80 Interventions for improving the appropriate use of imaging in people with musculoskeletal conditions: an update of a cochrane review. (4th December 2019) - Haas, Romi; Zadro, Joshua; Barnes, Hayley; Buchbinder, Rachelle; Green, Sally; French, Simon
Abstract : Background: Imaging is commonly performed for people with musculoskeletal conditions and is an important aspect of the management of these conditions. However, it may be used inappropriately and there is evidence of both underutilisation and overutilisation of imaging varying by specific condition. Inappropriate imaging can lead to unnecessary treatment, adverse health outcomes and waste valuable resources. Many different interventions can be used to improve imaging request behaviour of healthcare professionals. A Cochrane review of the effectiveness of these interventions in 2010 was inconclusive due to methodological weaknesses and heterogeneity of participants, interventions and outcomes of the included studies. Objective: Update the available evidence of the effects of interventions that aim to improve the appropriate use of imaging for people with musculoskeletal conditions. Selection criteria: Randomised controlled trials that evaluated interventions designed to improve appropriate use of imaging for participants with musculoskeletal conditions were included with no language restriction. Trials that assessed interventions designed to improve the appropriate use of imaging for diagnostic, screening or monitoring purposes, including assessing the response to treatment were included. We excluded studies of participants with traumatic musculoskeletal injuries as well as studies examining imaging accuracy. Interventions were classified as implementation strategies, delivery arrangements, financial arrangements, and/or governance arrangements according to the Cochrane Effective Practice and Organisation of Care taxonomy. Controls could be no intervention, usual care or another active intervention. Primary outcomes included quality of care (imaging use and downstream treatment), patient outcomes, resource use and adverse effects. We extracted outcome data immediately post-intervention and at one year post-intervention where possible. Search methods: We updated the search of the Cochrane Central Register of Controlled Trials, MEDLINE, Embase, CINAHL, Clinicaltrials.gov and WHO International Clinical Trials Registry Platform from 2007 until 21 June 2018. We also searched reference lists of included studies and relevant reviews; undertook citation searches of included studies; and contacted relevant authors. Data collection and analysis: Data extraction and risk of bias assessment is currently underway using standard Cochrane processes. Results: Thirty-six trials (14 new) were eligible for inclusion in this updated review. Twenty-four trials addressed under-use of imaging (all participants had a high likelihood of osteoporosis) and 12 trials addressed over-use (all aimed to reduce lumbar spine imaging; six trials additionally aimed to reduce imaging overuse in other joints). Sixty-six comparisons were conducted evaluating the effect of: implementation strategies (n=56); delivery arrangements (n=4); combined delivery arrangements and implementation strategies (n=5); and combined organisational arrangements and implementation strategies (n=1). All studies were conducted in high-income countries and most were conducted in a primary care setting (n=30). Complete results of this review will be presented at Preventing Overdiagnosis 2019. Conclusions: This review will incorporate the results of an additional 14 trials to the existing evidence base of the effects of interventions designed to improve the appropriate use of imaging for musculoskeletal conditions. Identifying effective interventions to improve use of imaging for people with musculoskeletal conditions has the potential to improve health outcomes for patients with musculoskeletal conditions and free up resources for evidence-based healthcare.